Microstructure modeling of high-temperature microcrack initiation and evolution in a welded 9Cr martensitic steel. (October 2019) - Li, M; O'Donoghue, PE; Leen, SB
Welded joints in tempered 9Cr–1Mo operating at elevated temperatures are well known to be prone to premature failure due to cracking in the heat-affected zone. This paper describes a crystal plasticity model to predict the microcrack initiation and evolution in the inter-critical heat-affected zone of 9Cr–1Mo welded steel at elevated temperature. A crystal plasticity finite element model indicates that the micro-cracks of 9Cr–1Mo steel mostly nucleate at prior austenite grain boundaries and boundary clustered regions. Inter-granular and trans-granular microcracking are shown to be the key predicted microdamage mechanisms from the current crystal plasticity model. A small amount of ferrite in the inter-critical heat-affected zone is shown to not only influence the microcrack initiation and evolution, but also significantly accentuate material degradation for a given applied load leading to premature failure at high temperature.